A Prospective Comparison of Molecular Diagnostic Techniques for the Early Detection of Cytomegalovirus in Liver Transplant Recipients - Patel, Robin; Smith, Thomas F.; Espy, Mark; Portela, Daniel; Wiesner, Russell H.; Krom, Ruud A. F.; Paya, Carlos V. (The Journal of infectious diseases, 1995)
Forty-one consecutive liver transplant recipients were studied by polymerase chain reaction (PCR) of serum and peripheral blood mononuclear cells, reverse transcription (RT)-PCR of peripheral blood mononuclear cells, and viral blood culture for symptomatic cytomegalovirus (CMV) infection. The techniques were also used to predict the occurrence ofCMV infection. For diagnosis of symptomatic CMV infection, the sensitivity and specificity of the different techniques were as follows:PCR of serum, 100% and 45%; RT-PCR, 25% and 97%; PCR of peripheral blood mononuclear cells, 83% and 35%; and blood culture, 83% and 86%, respectively. PCR of serum was positive in 83% of subjects with symptomatic infection before onset compared with 17% positive by blood culture. While viral blood culture was the best technique for the diagnosis of symptomatic CMV infection, peR of serum was best at predicting the development of symptomatic CMV infection.